2020
DOI: 10.1093/cdn/nzaa108
|View full text |Cite
|
Sign up to set email alerts
|

First Nations Food Environments: Exploring the Role of Place, Income, and Social Connection

Abstract: Abstract Background In Canada, few studies have examined how place shapes Indigenous food environments, particularly among Indigenous people living in southern regions of Ontario. Objective This paper examines and compares circumstances of food insecurity that imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…Other studies have also observed a significant reduction in lower‐income Canadian women's consumption in order to meet their children's food needs, which is linked to high levels of anxiety and stress as well as difficult child‐parent interactions (Tarasuk et al 2007). Studies of Indigenous mothers in particular have tended to focus on the urban setting (Baskin et al 2009; Cidro et al 2015) or northern Canada (Willows 2005); our study has identified a common experience of food insecurity and reduced consumption for lower‐income urban and on‐reserve First Nation mothers (Richmond et al 2020).…”
Section: Addressing Indigenous Food Insecurity Will Require Both Econmentioning
confidence: 81%
See 2 more Smart Citations
“…Other studies have also observed a significant reduction in lower‐income Canadian women's consumption in order to meet their children's food needs, which is linked to high levels of anxiety and stress as well as difficult child‐parent interactions (Tarasuk et al 2007). Studies of Indigenous mothers in particular have tended to focus on the urban setting (Baskin et al 2009; Cidro et al 2015) or northern Canada (Willows 2005); our study has identified a common experience of food insecurity and reduced consumption for lower‐income urban and on‐reserve First Nation mothers (Richmond et al 2020).…”
Section: Addressing Indigenous Food Insecurity Will Require Both Econmentioning
confidence: 81%
“…In Phase I, information on food security, diet, and food sources was collected through a survey administered to 228 First Nation respondents living in London, and at a nearby First Nation reserve. Findings from this survey revealed high levels of food insecurity among both urban and reserve‐based participants, with levels of food insecurity higher among those living in the city (Richmond et al 2020). Survey respondents also reported concerning experiences of hunger, and tendencies to purchase a majority of their foods from convenience stores.…”
Section: Community Engagement In Indigenous Food Researchmentioning
confidence: 95%
See 1 more Smart Citation
“…However, in order to better understand the ways through which vulnerability might manifest or be ameliorated within a specific complex adaptive system, location-specific, geography of place research approaches are also essential [ 48 , 49 ]. By compartmentalising the subsistence foodshed of Ulukhaktok, NT into components that can be appraised for their relative vulnerability in time and space, it is possible to identify transient or persistently at-risk dimensions within the system (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The FNFNES data, however, does not include First Nation individuals living in urban areas, Inuit or Métis. The CCHS identified 28.2% of Indigenous households as food insecure [17], but locally within southwestern Ontario, prevalence rates have been found to be much higher at 55% among those living in urban areas [27]. These results demonstrate that Indigenous families and individuals are at minimum more than twice as likely to experience food insecurity compared to the national average [17,26].…”
Section: Introductionmentioning
confidence: 99%